2019
DOI: 10.1002/mgg3.777
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing identifies a new mutation in the SLC19A2 gene leading to thiamine‐responsive megaloblastic anemia in an Egyptian family

Abstract: Background The Solute Carrier Family 19 Member 2 ( SLC19A2 , OMIM *603941) encodes the thiamine transporter 1 (THTR‐1) that brings thiamine (Vitamin B1) into cells. THTR‐1 is the only thiamine transporter expressed in bone marrow, cochlear, and pancreatic beta cells. THTR‐1 loss‐of‐function leads to the rare recessive genetic disease Thiamine‐Responsive Megaloblastic Anemia (TRMA, OMIM #249270). Methods In vitro stimulated blood lymphocytes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
(12 reference statements)
0
5
0
1
Order By: Relevance
“…Approximately half of the 60 SLC19A2 mutations associated with TRMA are missense variants (Supplemental Table 1 ) ( 5 , 25 ), yet few have been functionally characterized. In this study, we determined that three previously uncharacterized TRMA-associated SLC19A2 missense variants exhibited near-complete loss-of-function (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of the 60 SLC19A2 mutations associated with TRMA are missense variants (Supplemental Table 1 ) ( 5 , 25 ), yet few have been functionally characterized. In this study, we determined that three previously uncharacterized TRMA-associated SLC19A2 missense variants exhibited near-complete loss-of-function (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SLC19 is a folate/thiamine transporter family, and there are three members (SLC19A1-3), of which SLC19A1 transports folates but not thiamine, and the other two transport thiamine but not folates (Zhao and Goldman, 2013). Mutations in the SLC19A2 gene, encoding thiamine transporter 1 (THTR1), were reported to be associated with thiamine-responsive megaloblastic anemia (TRMA) (Scharfe et al, 2000;Ozdemir et al, 2002;Ghaemi et al, 2013;Setoodeh et al, 2013;Sun et al, 2018;Amr et al, 2019), which is characterized by early-onset diabetes mellitus, anemia, and sensorineural deafness.…”
Section: Slc19a2mentioning
confidence: 99%
“…familial Mediterranean fever (MEFV gene) [120], thiamine-responsive megaloblastic anemia (SLC19A2 gene) [121], cerebellar atrophy and developmental delay (PLA2G6, KIF1A and MOCS2A genes) [122], micro-/anophthalmia (VSX2, SOX2, and FOXE3 genes) [123], RAGdeficiency (RAG1 and RAG2 genes) [124], auriculocondylar syndrome (PLCB4, GNAI3, and EDN1 genes) [125], ectodermal dysplasia (EDA, EDAR, and EDARADD genes) [126], 3phosphoglycerate dehydrogenase deficiency (PHGDH gene) [127], carpenter syndrome (RAB23 gene) [128], disorders/differences of sex development (NR5A1, CYP19A1, AMH, AMHR2, WT1, HHAT, and FANCA and in the X-linked genes KDM6A and ARX genes) [129] and autosomal recessive polycystic kidney disease (PKHD1 gene) [130]. WES studies in Iraqi people revealed associated genes of epileptic encephalopathy (SLC13A5 gene) [131],…”
Section: P R E P R I N Tmentioning
confidence: 99%